EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE DENGAN PENDEKATAN ILMIAH PADA POKOK BAHASAN LIMIT FUNGSI DITINJAU DARI ADVERSITY QUOTIENT PESERTA DIDIK SMA NEGERI KABUPATEN BANYUMAS TAHUN PELAJARAN 2013/2014 - Dian Ratna Ariyani; Mardiyana Mardiyana; Dewi Retno Sari S (Jurnal Pembelajaran Matematika, 2015)
Abstract : The purposes of the  research  were  to  know:  (1)  which  learning  models  -think pair share cooperative learning model with scientific approach (TPS SA), think pair share cooperative learning (TPS), and direct learning model (DL)-that will give the best learning mathematics result;  (2)  which level of students adversity  quotient  (AQ) -quitter, camper, and climber-that will give the best mathematics learning result; (3) which learning models -TPS SA, TPS, and DL- that will give the best learning mathematics result at categories AQ; (4) which level of students AQ -quitter, camper and climber- that will give the best learning mathematics result at categories learning models. The research used a quasi-experimental designed with population was all students of eleventh grade science in Banyumas in the academic year 2013/2014. The technique sampling was stratified cluster random sampling. The instrument used to collect the data was a questionnaire of AQ and math achievement tests. Hypothesis test used two way analysis of variance with unequal cells. Based on the analysis we concluded: (1) TPS SA provided a better learning achievement than only TPS and direct learning, TPS provided a better learning achievement than direct learning; (2) climber students had a better learning achievement than camper and quitter, camper had a better learning achievement than a quitter; (3) for climber students, TPS SA, TPS, and  direct learning provided the same good learning performance, for camper students, TPS SA provided a better learning achievement than TPS and direct learning, TPS provided a better learning achievement than direct learning, for quitter students, TPS SA, TPS, and  direct learning provided the same good learning performance; (4) in TPS SA, climber students had an academic achievement as good as camper students, climber students had a better learning achievement than quitter students, camper students had a better learning achievement than quitter students, in TPS, climber students had a better learning achievement than quitter and camper, camper students had a better learning achievement than quitter, in direct learning, climber students had a better learning achievement than quitter and camper, camper students had academic achievement as good as quitter.Keywords: Cooperative  Learning,  Scientific  Approach,  Think  Pair  Share  with scientific approach, Adversity Quotient (AQ).